Moving Along and Beyond the Spectrum: Creative Group Therapy for Children With Autism - Vaisvaser, Sharon (Frontiers in Psychology, 2019)
Group therapy for autism confronts the core of the syndrome. Non-directed dynamic approaches, in which moment-to-moment spontaneous expressions drive the content of group sessions, are even more intricate. The implementation of nonverbal creative techniques holds the key to self-expression and self-other exploration, promoting communication and play. This manuscript offers an integrative conceptual model and a case report regarding such mind-body therapeutic perspective. The creative arts intervention is presented via a small group of young minimally verbal children with autism, deprived of communicative language, offering an interdisciplinary perspective to delineate group challenges and rationale, process and outcomes. Vignettes are provided to illustrate the group development. A thorough discussion follows, addressing three intertwining axes: firstly, the implications of nonverbal creative means are considered; secondly, the psychophysiological processes set in motion through sensory-motor experiences are deliberated; and thirdly, the emergence of 'moments of meeting' and spontaneously-generated playful group activities are enlightened.